2021
DOI: 10.3390/cancers13051053
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin for Patients with Advanced Soft Tissue Sarcoma: A Non-Interventional, Retrospective, Multicenter Study of the Italian Sarcoma Group

Abstract: The Italian Sarcoma Group performed this retrospective analysis of patients with advanced soft tissue sarcoma, pretreated with ≥1 anthracycline-based treatment, and treated with trabectedin every three weeks. Primary endpoint was to describe real-life use of trabectedin across Italy. Secondary endpoints included objective response rate (ORR) and safety. Overall, 512 patients from 20 Italian centers were evaluated. Leiomyosarcoma (37.7%)/liposarcoma (30.3%) were the most prevalent histological types (abbreviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
7
16
0
Order By: Relevance
“…Our results show a median PFS of 3.6 months for all patients, with a 4.2-month median for those with L-sarcoma and a 3.4-month median for those with non-L-sarcoma. These results are similar to the results of phase III trials [7,8] and the compassionate use program [17], although they are shorter than those of some more recent trials [15,16].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results show a median PFS of 3.6 months for all patients, with a 4.2-month median for those with L-sarcoma and a 3.4-month median for those with non-L-sarcoma. These results are similar to the results of phase III trials [7,8] and the compassionate use program [17], although they are shorter than those of some more recent trials [15,16].…”
Section: Discussionsupporting
confidence: 83%
“…Most researchers who evaluated the influence of metastases on survival concluded that the metastatic pattern did not affect survival [15,17]. However, our research showed that the number of different metastatic sites as a surrogate marker of disease burden was the most significant factor affecting survival along with the tumor subtype.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A number of clinical phase I studies have found that it has a good effect on ovarian cancer when used alone or in combination with other chemotherapeutic drugs, such as cisplatin [ 68 , 69 , 70 ]. Phase II and III clinical studies have shown that trabectedin alone or in combination with other anticancer drugs is effective in soft tissue tumors, especially liposarcoma and leiomyosarcoma, and prolongs the survival time of the patients [ 30 , 71 , 72 , 73 ].…”
Section: Trabectedin/et-743mentioning
confidence: 99%
“…Trabectedin is a tetrahydroisoquinoline alkaloid that was originally extracted from a marine organism, the Tunicate Ecteinascidia turbinate , and is now synthetically produced by PharmaMar (Spain) [ 15 , 16 , 17 ]. Trabectedin, a registered antitumor agent, is used in the clinic for the second‐line treatment of soft tissue sarcoma, especially liposarcoma, and for relapsed platinum‐sensitive ovarian cancer patients, in combination with liposomal doxorubicin [ 18 , 19 , 20 , 21 , 22 ]. The mechanism of action of trabectedin on cancer cells is complex and different from that of other anticancer agents.…”
Section: Introductionmentioning
confidence: 99%